STUDI TENTANG PERANAN GURU PPKn DALAM MENINGKATKAN SIKAP CINTA TANAH AIR DI LINGKUNGAN SMA NEGERI 2 RIMBA MELINTANG KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Yusni Wati; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The role of PPKn teachers is very important in addition to teaching science, PPKn teachers also play a major role in shaping the character of students, so that students get a deep understanding and appreciation of values. Things that need to be considered as a teacher must be able to instill, have a love for the homeland so that the identity of the Indonesian nation remains. This study aims as follows: To find out how the Role of PPKn Teachers in Improving the Love Attitude of the Motherland in the Environment of Rimba Melintang 2 High School. To find out how the level of attitude of love for the homeland of students in the Rimba Melintang 2 High School.To find out how the relationship between the role of PPKn teachers towards the attitude of love for the homeland in the Rimba Melintang 2 Public High School environment. The subjects of this study were all 5 people from the PPKn teachers of SMA 2 Rimba Melintang, and students of class X which amounted to 138 students, and class XI which consisted of 103 students. The sample in this study was taken based on random sampling techniques with a number of subjects of 10% from 241 students. Because the number of teachers is less than 100, the total number of PPKn teachers is used as research samples (population researchers). Data is collected through observation, questionnaires, interviews, and documentation. In analyzing the data using quantitative descriptive techniques using statistical tests. The results showed that there was a significant effect of the role of PPKn teachers in improving the attitude of love for homeland in the Rimba Melintang 2 Public High School environment, this was evidenced by the results of simple linear regression tests between variables X and Y variables, obtained Fcount (12,813) and Ftable values (4,30) shows that F_count> from F_tabel, so Ho is rejected and Ha is accepted so the hypothesis testing is accepted. And this influence is strong because the value of r count is 0.607. Key Words: Role, Teacher PPKn, Attitude of Love for the Motherland.